IMPLEMENTASI MANAJEMEN KESISWAAN DALAM RANGKA PENINGKATAN SUMBER DAYA MANUSIA UNGGUL DI SEKOLAH MENENGAH PERTAMA NEGERI I KOTA MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This Research aims to determine the student management in junior high school 1 (SMP Negeri 1) Magelang city in order to improve the quality human resource. In detail, this research aims to determine: new admission, management quality improvement of human resources (students) in accordance with the curriculum, extracurricular activities and fostering interest student talent and the obstacles that are faced.This research uses qualitative research with descriptive analytical approach. The research was conducted in June – July 2014. The data were collected through observation, interviews and documentation. The Sources of data consisting of the principal, vice-principal of student field. The data analysis was consist of reduction, display, and conclusion / drawing / verification.The results showed that: first, the implementation of student management in order to increase the superior human resources has been running well. Acceptance of the new set in online way as Education Department of Magelang City System. Second, developing the quality of student through the implementation of teaching and learning activities or through extracurricular activities carried out systematically. Teaching and learning activities tailored to the curriculum in 2013. Third, the management of extracurricular activities carried out systematically. The school and extracurricular participant select a target to win the competition. School provides a means of activities, trainer and coaches, and scheduling of activities and special briefing for students who will advance in the competition. Full implementation by teacher coaches and trainers. Fourth, the obstacles that are faced, such as the limitations of coaches and basketball time in extracurricular activities.